The autophagy-lysosomal pathway is involved in TAG degradation in the liver: the effect of high-sucrose and high-fat diet - Cahová, M; Daňková, H; Páleníčková, E; Papáčková, Z; Kazdová, L (Folia biologica, 2010)
This study was designed to test the role of liver lipases in the degradation of liver triacylglycerols (TAG) and to determine the effect of dietary induced TAG accumulation in the liver on regulation of their lipolysis. Male Wistar rats were administered high-fat or high-sucrose diet for two weeks. Individual lipases (HL; TGH; LAL) were identified according to their different pH optimum. Administration of both diets resulted in liver TAG accumulation (HFD >>> HSD). The only lipase capable to hydrolyse intracellular TAG was LAL. On standard diet, LAL activity towards both endogenous and exogenous substrates was up-regulated in fasting and downregulated in fed state. The intensity of autophagy determined according to the LC3-II/LC3-I protein ratio followed a similar pattern. HFD led to an increase of this ratio, elevation of LAL activity in phagolysosomal fraction and abolishment of fasting/fed-dependent differences. LAL activity significantly correlated with ketogenesis in all groups (r = 0.86; P < 0.01). In the HFD group, we determined the enhanced release of lysosomal enzymes (glucuronidase, LAL) into the cytosol. Dgat-1 expression was up-regulated in HFD- and HSD-fed groups, which indicates increased FFA esterification. We demonstrated that LAL is a dominant enzyme involved in degradation of intracellular TAG in the liver and its translocation into the fraction of active (auto)phagolysosomes is stimulated by diet-induced TAG accumulation. Autophagy is stimulated under the same conditions as LAL and may represent the mechanism ensuring the substrate enzyme contact in autophagolysosomes. In fatty liver, destabilization of (auto)phagolysosomes may contribute to their susceptibility to further stress factors.
Keywords: Liver; Animals; konzumní sacharóza; Lysosomes; Autophagy; Rats, Wistar; játra; Fatty Liver; lyzozomy; triglyceridy; dietní tuky; Triglycerides; sterolesterasa; Sterol Esterase; ztučnělá játra; Dietary Sucrose; autofagie; Male; krysa rodu Rattus; zvířata; mužské pohlaví; Dietary Fats; Rats; potkani Wistar